A discussion of the market and policy failures associated with the adoption of herbicide-tolerant crops. Issue 5 (3rd September 2019) - Desquilbet, Marion; Bullock, David S.; D'Arcangelo, Filippo Maria
ABSTRACT: Weed control in the U.S. Midwest has become increasingly herbicide-centric due to the adoption of herbicide-tolerant (HT) crops in the 1990s. That integrated weed management (IWM) practices, including ecological and mechanical controls, are scarcely used is concerning. IWM would be a more sustainable form of farming for two reasons. First, it would reduce the negative health and environmental externalities associated with herbicide use. Second, it would reduce the selection pressure on weed populations and the development of weed resistance to some herbicides, thereby reducing the uncertainty of the long-term effectiveness of herbicidal weed control. In this context, we develop an economic framework to clarify the interplay among the different market failures that either contribute to the herbicidal 'lock-in' or make it problematic. We then analyse the evidence for and perceptions of these market failures based on twenty-four semi-structured interviews with farmers and experts conducted in 2017, as well as on discussions in the academic literature. To this end, we put into perspective the possible self-reinforcing effects in the adoption path of HT crops, such as increasing farm size, changes in farm equipment, increasing incentives for simplified crop rotations, and the loss of practical knowledge of IWM practices.